1998
DOI: 10.1007/s005950050300
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Management of Microwave Coagulation Therapy for Primary and Metastatic Liver Tumors

Abstract: Microwave coagulation therapy (MCT) has been widely used, both percutaneously and directly, as effective minimal invasive therapy for liver tumors. To facilitate the use of MCT, we describe the complications we have encountered, and their possible management and prophylaxis. MCT was performed for 42 patients with hepatocellular carcinoma (HCC) and for 29 with metastatic liver tumors, following which complications developed in 14.2% and 20.6% of the HCC and metastatic groups, respectively. The complications inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 17 publications
1
54
0
Order By: Relevance
“…Major complications include bile duct stenosis, uncontrollable bleeding, liver abscess, colon perforation, skin burn and tumor seeding, etc. [12, 26,52,53,54]. Postoperative death due to liver failure was reported for intraoperative MWA [42], whereas no treatment-related deaths for laparoscopic and percutaneous MWA have been reported to date.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Major complications include bile duct stenosis, uncontrollable bleeding, liver abscess, colon perforation, skin burn and tumor seeding, etc. [12, 26,52,53,54]. Postoperative death due to liver failure was reported for intraoperative MWA [42], whereas no treatment-related deaths for laparoscopic and percutaneous MWA have been reported to date.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…It is usually self-limiting and seldom requires transfusion or laparotomy 114 . However, Curley et al 106 93 reported one instance of acute cholecystitis after radiofrequency ablation; biliary fistula and biloma formation have been described after microwave therapy 104,122 . No biliary complications have been reported after ILP therapy.…”
Section: Complicationsmentioning
confidence: 98%
“…Thermal ablation is a well tolerated procedure, with a reported complication rate of 3-7 per cent in most series of radiofrequency and ILP ablation, and of 11-23 per cent in those describing microwave thermal ablation 118,122 . This difference is probably due to the latter therapy being employed predominantly in patients with cirrhosis.…”
Section: Complicationsmentioning
confidence: 99%
“…The complications such as slight pain, fever, and subcutaneous hematoma (total rate about 20.6%) can be experienced immediately after MCT, and in general, special treatment is unnecessary (Matsukawa et al 1997;Shimada et al 1998). …”
Section: Microwave Coagulation Therapymentioning
confidence: 98%